The Three S's for Aptamer‐Mediated Control of DNA Nanostructure Dynamics: Shape, Self‐Complementarity, and Spatial Flexibility. (10th August 2018) - Shiu, Simon Chi‐Chin; Kinghorn, Andrew B.; Sakai, Yusuke; Cheung, Yee‐Wai; Heddle, Jonathan G.; Tanner, Julian A.
Abstract: DNA aptamers are ideal tools to enable modular control of the dynamics of DNA nanostructures. For molecular recognition, they have a particular advantage over antibodies in that they can be integrated into DNA nanostructures in a bespoke manner by base pairing or nucleotide extension without any complex bioconjugation strategy. Such simplicity will be critical upon considering advanced therapeutic and diagnostic applications of DNA nanostructures. However, optimizing DNA aptamers for functional control of the dynamics of DNA nanostructure can be challenging. Herein, we present three considerations—shape, self‐complementarity, and spatial flexibility—that should be paramount upon optimizing aptamer functionality. These lessons, learnt from the growing number of aptamer–nanostructure reports thus far, will be helpful for future studies in which aptamers are used to control the dynamics of nucleic acid nanostructures. Abstract : The dynamics of DNA nanostructures can be controlled by aptamers. Three considerations are highlighted to optimize aptamers for this application: shape, self‐complementarity, and spatial flexibility. There is significant potential to build better controls for nucleic‐acid‐mediated molecular recognition events through the application of aptamers for therapeutic and diagnostic purposes.